Enhancing reading comprehension and motivation through Think-Pair-Share: Classroom action research in an Indonesian EFL context - Pratolo, Bambang Widi; Bao, Dat; Palaguna, Suhendri (Universitas Ahmad Dahlan, 2025)
Improving students' reading comprehension remains a persistent challenge in EFL classrooms, particularly where learners exhibit low motivation and limited engagement. This study investigated the effectiveness of the Think–Pair–Share (TPS) cooperative learning strategy in an Indonesian secondary EFL classroom. Using a Classroom Action Research (CAR) design, the intervention was conducted in two cycles, each consisting of planning, acting, observing, and reflecting stages. Data were collected through a mixed-methods approach. Quantitative evidence came from pre-tests and post-tests of reading comprehension, while qualitative data were obtained from classroom observations, field notes, and interviews. The findings showed substantial improvements in both motivation and understanding. Students' mean reading scores increased from 57.22 in the pre-test to 78.26 in Cycle II, with the number achieving the passing grade rising from three to fifteen. Variability decreased, indicating more consistent achievement across the class. Qualitative results revealed a transformation from passive and disengaged learners to confident and motivated participants who valued collaboration and peer support. The study concludes that TPS is effective not only in enhancing comprehension but also in fostering a student-centered and inclusive learning environment. Teachers are encouraged to integrate TPS with explicit scaffolding and adaptive sharing formats to maximize equity and engagement in reading instruction.